Avedis Donabedian: The Giant (Epidemiology, Biostatistics, and Public Health, 2022)
“Giant” is the most frequent word in commemorating Avedis Donabedian. Rarely there was such agreement among scholars worldwide to define the role of a scientist in the field of Public Health. And it’s impossible to disagree. Avedis Donabedian had a really huge role in the progress in Public Health studies. It’s not exaggerated even to say that his insights influenced all scientific research.